Nuclear Factor–Erythroid-2–Related Factor 2 in Aging and Lung Fibrosis - Swamy, Shobha M. (Am J Pathol, 2016)
Aging and age-related diseases have been associated with elevated oxidative stress, which may be related to increased production of reactive species and/or a deficiency in antioxidant defenses. The nuclear factor-erythroid-2–related factor 2 (Nrf2)-mediated antioxidant response pathway maintains cellular reduction-oxidation homeostasis by inducing the transcription of an array of cytoprotective genes. However, there is evidence of impaired Nrf2 response in aging contributing to age-related fibrotic diseases. Herein, we review mechanisms for the dysregulation of Nrf2 signaling in aging. This understanding will pave the way for the design of novel therapeutic strategies that restore Nrf2 signaling to reestablish cellular homeostasis in aging and age-related fibrotic diseases.